Order of entry and performance in new markets - Lambkin, Mary (Strategic Management Journal, 1988)
A prevalent view among both academics and managers is that pioneers enjoy an enduring advantage over all later market entrants. The study reported in this paper tests this assertion by comparing the behavior and performance of three entrant categories—namely, pioneers, early followers and late entrants. A population ecology model is used to develop a set of hypotheses and these are tested on samples of start-up and adolescent businesses from the PIMS data base. The results show the three entrant categories to have significantly different strategic profiles and performance levels, with pioneers tending, on the average, to outperform later entrants.